Cytotoxic and Antioxidant Activity of Mimosa verrucosa Benth. - Romanoski, Vanessa Silva; Santos, Rauldenis Almeida Fonseca (Orbital: The Electronic Journal of Chemistry, 2017)
The present work describes the antioxidant and cytotoxic properties of the ethanolic extracts of the leaves and stems of Mimosa verrucosa Beth. (Fabaceae) found in Northeast Brazil. The antioxidant activity was evaluated using the stable radical sequestration essay of 2,2-diphenyl-1-picrylhydrazyl (DPPH), demonstrating that the leaves had the highest antioxidant activity (IC50= 372.7 ± 0.3 μg.mL-1) and the cytotoxic activity was obtained by evaluating the mortality of Brine shrimp larvae, revealing the highest cytotoxic potential of the roots (DL50 = 145.5 ± 21.5 μg.mL-1). The analysis of the chromatograms obtained in HPLC-DAD and the thin layer chromatography plates with specific reagents indicated the presence of steroids, flavonoids, saponins and tannins in the different extracts, to which the antioxidant and cytotoxic activities were attributed. DOI: http://dx.doi.org/10.17807/orbital.v9i2.868